A comparison of the accuracy of various methods of postnatal gestational age estimation; including Ballard score, foot length, vascularity of the anterior lens, last menstrual period and also a clinician's non-structured assessment - Stevenson, Alexander Graham (Department of Paediatrics and Child Health, 2021)
Rationale Gestational age is a strong determinant of neonatal mortality and morbidity. Early obstetric ultrasound is the clinical reference standard, but is not widely available in many developing countries. There is a well recognised need to identify reliable and simple methods of postnatal gestational age estimation. Methods A prospectively designed methods comparison study in a tertiary referral hospital in a developing country. Early ultrasound (<20 weeks) was the clinical reference standard. Methods evaluated included anthropometric measurements (including foot-length), vascularity of the anterior lens, the New Ballard Score and Last Menstrual Period. Clinicians' non-structured global impression “End of Bed” Assessment was also evaluated. Results 106 babies were included in the study. Median age at birth was 34 weeks (IQR 29-36). Ballard Score and “End of Bed” Assessment had a mean bias of -0.14 and 0.06 weeks respectively but wide 95% limits of agreement. The physical component of the Ballard score, the total Ballard score and Foot-length's ability to discriminate between term and preterm infants gave an AUROC of 0.97, 0.96 and 0.95 respectively. Discussion Although “End of Bed” Assessment and Ballard score had small mean biases, the wide confidence intervals render the methods irrelevant in clinical practice. Foot-length was particularly poor in Small for Gestational Age infants. None of the methods studied were superior to a non-structured clinician's informal “End of Bed” Assessment. Conclusion None of the methods studied met the a priori definition of clinical usefulness. Improving access to early ultrasound remains a priority. Instead of focusing on chronological accuracy, future research should compare the ability of early ultrasound and Ballard score to predict morbidity and mortality.